Farmers’ perspective toward a demand led yam breeding in Nigeria - Kalu, C.; Nnabue, I.; Edemodu, A.; Agre, A.P; Adebola, P.O.; Asfaw, A.; Obidiegwu, J.E. (Frontiers Media, 2023)
This study seeks to increase the efficiency of yam breeding practice using farmers’ insight at the trait and socioeconomic levels. A three-staged multisampling procedure was employed and 792 yam farmers from four geopolitical zones, comprising 10 states and the Federal Capital Territory, Abuja in Nigeria were randomly selected. Farmer’s preference criteria and factors pertinent to improving the efficiency of yam breeding in Nigeria were documented. The data obtained were analyzed using a 5-point Likert scale to identify major traits farmers consider in the yam cultivar selection decision. Kendall’s coefficient of concordance was used to measure the degree of agreement of ranking among the farmers. Factors influencing farmers’ trait preference for yam cultivars were evaluated using a multinomial-ordered logistic regression model. The result revealed that yam varieties with high germination rates, disease-free quality, big tuber sizes, early maturity, and good pounding attributes are held in high esteem. The most critical constraint limiting the production of yam in the study area includes pest and disease attack, climate change, high cost of seed yam, high cost of staking, and weed infestation. Sex, age, access to credit, membership to yam association, total land owned, and years of experience as a yam farmer significantly influence farmers’ ability to select yam cultivars with preferred attributes. A strategic effort needs to be given to these farmers’ desired yam attributes and factored into developing improved yam varieties for increased adoption and enhanced food security in Nigeria.